ASSESSMENT OF THE EFFECTIVENESS OF POSTOPERATIVE PAIN RELIEF IN ELDERLY AND SENILE PATIENTS WITH CIRCULATORY INSUFFICIENCY - Z.T. Gaziev ,; O.Sh. Sayitov ,; A.R. Khojaev ,; Sh.M. Valiev , (Central Asian Journal of Medicine, 2025)
Patient-controlled analgesia is an alternative to traditional analgesic regimens for geriatric patients with circulatory insufficiency who have undergone lower extremity surgery. This method should become one of the primary approaches for postoperative pain management, as it ensures adequate analgesia and has a positive impact on hemodynamics.